2022
DOI: 10.4269/ajtmh.21-0727
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Healthcare Worker Density on Maternal Health Service Utilization in Sub-Saharan Africa

Abstract: Facility births and antenatal care (ANC) are key to improving maternal health. This study evaluates the relationship between physician and nurse/midwife densities and the use of key maternal health services across sub-Saharan Africa (SSA). The authors matched individual-level maternal health service indicators from Demographic and Health Surveys between 2008 and 2017, to country-level physician and nurse/midwife per-capita densities, across 35 SSA countries. The authors performed univariate and multivariate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The availability of nurses may lead to the increased use of preventative health care services and thus improved health outcomes. 56 Previously and in the context of the United States, it has been shown that the density of nurses is associated with the reduction in preventable and overall mortality. 57 , 58 , 59 Similar findings have emerged from other high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of nurses may lead to the increased use of preventative health care services and thus improved health outcomes. 56 Previously and in the context of the United States, it has been shown that the density of nurses is associated with the reduction in preventable and overall mortality. 57 , 58 , 59 Similar findings have emerged from other high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that more women were now delivering in facilities and coming in for ANC and family planning because of the midwives' work. Evidence shows that increased healthcare worker density is associated with increased use of ANC and facility birth ( 18 ). Delivery in a health facility with a skilled health worker and good quality ANC contributes to reducing maternal and neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Yet, a single person has multiple SRHR needs and they often interact with one another, such as gender based violence and women's risk of HIV acquisition, condom use at last sex amongst adolescents and teenage pregnancy; and number of skilled health professionals, proportion of births attended by skilled birth personnel and maternal mortality. 3 , 4 , 5 However, data are not always easily available for all countries to allow for comparisons and build on best practices. Given that more than half of the world's population continues to have limited or no access to sexual and reproductive health services over their lifetime, many health systems actions including access to quality data remain important to advance SRHR.…”
Section: Introductionmentioning
confidence: 99%
“…Given that more than half of the world's population continues to have limited or no access to sexual and reproductive health services over their lifetime, many health systems actions including access to quality data remain important to advance SRHR. 5 …”
Section: Introductionmentioning
confidence: 99%